Analysis Of Work Accident Risks in The Construction Of Sutet Steel Towers Using the JSA (Job Safety Analysis) Method - Yasinta, Rezi Berliana; Fadhilah, Muhammad Rasyid; Buchori, Syakiila Az Zahra Al; Hasanah, Nadilla Hikmatul; Hermawan, Fajar (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
Construction activities inherently carry risks that can lead to accidents, causing delays, injuries, and financial losses. In high-risk projects such as High Voltage Direct Current (HVDC) transmission tower construction, inadequate safety practices and low awareness of Occupational Health and Safety (OHS) increase the potential for workplace accidents. This qualitative descriptive study analyzes potential work hazards in HVDC tower construction using secondary data and the Job Safety Analysis (JSA) method. Four main work processes—tower leg, body, and cross arm installation, and cable pulling—were assessed. Results show that all activities involve significant risks, with falls from height, falling objects, and puncture/scratch injuries being the most common. There are 6 activities in the Extreme category, 3 activities in the High category, 14 activities in the Moderate category, and 8 activities in the Low category. The main risks are falling from heights, being struck by materials, and injuries caused by work tools, which are exacerbated by low use of PPE, weak supervision, and lack of worker compliance. The solution to this problem lies in control priority, where there are four solutions: elimination, engineering, administration, and personal protective equipment control.